14 Myocardial dysfunction in ANCA vasculitis measured by two-dimensional speckle tracking echocardiography. (28th September 2016) - Bajrangee, A; Mahabir, S; King, G; Cuddy, S; Feighery, C; Maree, A; Conlon, N; Murphy, RT
Abstract : Aim: Myocardial involvement in patients with systemic vasculitis portends a poorer prognosis. We sought to determine the extent of myocardial dysfunction in Granulomatosis with polyangitis and Churg Strauss disease using speckle tracking and strain imaging. Methods: 20 patients and 22 controls with no prior cardiac history were recruited from December 2015 to April 2016. Baseline demographics recorded included age, sex, cardiovascular risk factors, time since diagnosis, immunosuppressive therapy and vasculitis damage index score (VDI). We performed transthoracic echocardiography using Vivid 7 GE machine along with twelve lead electrocardiograms (ECG) and biochemical analysis at the study visit. A single blinded operator utilising Echo Pac 11 software performed offline analysis of strain and speckle tracking measurements. Results: Mean age of the vasculitis group was 56 ± 10 years with 50% being male, while mean age of controls was 53 ± 9 years with 55% male. There were no significant differences between groups in age, incidence of hypertension (p = 0.3) or diabetes (p = 0.6). Radial strain was significantly reduced in the vasculitis cohort (P = 0.05). The vasculitis cohort also showed a non-significant reduction in longitudinal strain and abnormal diastology as reflected in a reduction in tissue Doppler E' velocities, decreased transmittal E/A ratio and increased E/E' ratio when compared to controls (Table 1 ). There were negative correlations between increasing VDI score and reduction in mitral inflow velocities r = −0.5 (p = 0.02), number of clinical relapses and tissue Doppler E' r = −0.6 (p = 0.009) and length of cyclophosphamide use with tissue Doppler E' r = −0.5 (p = 0.02). Conclusion: This is one of the largest studies investigating myocardial dysfunction in ANCA positive vasculitis. Patients demonstrated a reduction in radial strain and evidence of abnormal left ventricular relaxation. This may be indicative of underlying cardiac involvement.